Panic Disorder with Choking Phobia: A Case Report - Patricia Wulandari (Scientia Psychiatrica, 2020)
Panic disorder is a form of anxiety disorder characterized by repeated panic attacks and preoccupied with worrying that a panic attack will occur. Panic attacks are characterized by fears of a disaster or loss of self-control even though there is really nothing to worry about. Other symptoms experienced during a panic attack are heart palpitations (similar to a heart attack), shortness of breath, feelings of suffocation, and the body feels weak. If this disorder is not detected early, it will affect the daily life of the patient. This case report presents the case of a 34-year-old woman who experiences symptoms of panic disorder with choking phobia that is managed with antidepressants and cognitive behavior therapy. In addition, there is discussion of differential diagnosis and the role of cognitive behavior therapy in handling this case.